A48 NOVEL INTESTINAL ORGANOID-DERIVED MONOLAYERS TO MODEL CELIAC EPITHELIUM IN VITRO. (15th March 2019) - Rahmani, S; Vahedi, F; Galipeau, H J; Su, H; Chirdo, F G; Didar, T F; Verdu, E
Abstract: NOT PUBLISHED AT AUTHOR'S REQUEST Funding Agencies: CIHRSupported by a grant by the Farncombe Family Digestive Health Research Institute to EFV.